Relative depth-doses from square and rectangular Y-90 beta applicators used in skin cancer therapy (Brazilian Journal of Radiation Sciences, 2020)
Plaques containing beta-emitting isotopes have several medical applications. In particular, due to the short range of beta particles and the rapid fall off of dose rates they are suitable to be used in small and superficial skin cancer therapy, killing the tumor cells and preserving the underlying healthy structures. The analytical/numerical beta-point dose function formalism is used to a simple estimate of the relative dose rates around square and rectangular beta applicator containing the Yttrium-90 isotope. Maximum differences in relative dose rates along central axis of 13% at 6.6 mm depth and 20% at 5 mm depth were found, respectively, for the square and rectangular plaques as compared with the literature measurements data. Results have also indicated that for both plaques dose rates fall off to 50%  of the reference value at about  2 mm depth; drop to just 10% at 4.5 mm depth, and become  zero from 8 mm on. This fact confirms that these sources are suitable to  be used in superficial skin cancer therapy. The method presented here may be used to estimate the relative dose rates around square and rectangular Y-90 beta applicators in a simple and fast way.
Keywords: Skin cancer therapy; beta particles; Y-90 applicator; beta-point dose function; relative depth-dose calculation